Longitudinal follow-up of muscle echotexture in infants with congenital muscular torticollis. Issue 6 (February 2017) - Hu, Ching-Fang; Fu, Tieh-Cheng; Chen, Chung-Yao; Chen, Carl Pai-Chu; Lin, Yu-Ju; Hsu, Chih-Chin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Unilateral fibrous contracture of the sternocleidomastoid (SCM) muscle is the major pathophysiology in infants with congenital muscular torticollis (CMT). Physical examination is not always sufficient to detect minimal muscle fibrosis in involved SCM muscles. A prospective study for SCM muscle fibrosis in CMT infants by quantifying echotexture and muscle thickness during the course of treatment is highlighted in the study. Convenience samples of 21 female and 29 male infants with CMT, who were 1 to 12 months old, underwent physiotherapy for at least 3 months and were followed for 4.7 ± 0.4 months. All infants had at least 2 clinical assessments and ultrasonographic examinations for bilateral SCM muscles during follow-up. The K value, derived from the difference in echo intensities between the involved and uninvolved SCM muscles on longitudinal sonograms, was used to represent the severity of muscle fibrosis. Bilateral SCM muscle thickness and ratio of involved to uninvolved muscle thickness (Ratio I/U) were obtained simultaneously. Clinical outcome was also recorded. No subjects underwent surgical intervention during follow-up. The K value decreased from 6.85 ± 0.58 to 1.30 ± 0.36 at the end of follow-up ( P < 0.001), which reflected the decrease of muscle fibrosis. The Ratio I/U decreased from 1.11 ± 0.04 to 0.97 ± 0.02 during treatment, which was possibly related to the increased uninvolved SCM muscle thickness. In conclusion, echotexture is an efficient indicator for reflecting a wide degree of muscle fibrosis in infants with CMT and is informative during the treatment course.